Merchants, bankers, governors British enterprise in Singapore and Malaya, 1786-1920 - Drake, P. J. (Peter Joseph) (World Scientific, 2018)
"This is the story of British enterprise in Singapore and Malaya from 1786 to 1920, when British vision, zeal and drive developed Penang, then Singapore and, finally, the peninsular Malay States. In the initial years, commerce and finance were paramount. The seeds of these commercial activities had been planted initially in the days of the East India Company but later, and more importantly, by individual merchant firms, supported by credit from London. These merchants were the driving force of British investment and development on the Malay Peninsula. While the contributions of the Malays, Indians and, especially, the Chinese to economic development should not be under-rated, in the period under review, their activities were steered and monitored by the British. This book presents an original and coherent account of British Enterprise in Singapore and Malaya in an important historical period and includes substantial new material from primary records of merchant firms and banks which will be of great interest to students, professionals as well as the general public."--Publisher's website